Late Mesozoic Intracontinental Deformation in the Northern Margin of the North China Craton: A Case Study From the Shangyi Basin, Northwestern Hebei Province, China - Yang, Qian; Shi, Wei; Hou, Guiting; Zhang, Yu; Zhao, Yilin (Frontiers in Earth Science, 2021)
During the late Mesozoic, the East Asian continent underwent a complex tectonic history due to multiple plate convergence. How to respond to the multiple plate convergence in the North China Craton (NCC) remains unclear. Here we undertook field geological investigations and fault-slip vectors analysis of the Shangyi Basin in the western Yanshan fold and thrust belt, northern margin of the NCC. Combined with new geochronological data, we delineate three phases of intracontinental deformation in the area: (1) NW-SE compression during the Late Jurassic to earliest Cretaceous (ca. 151-141 Ma); (2) NW-SE extension during the middle–late Early Cretaceous (ca. 135-110 Ma); and (3) NE-SW compressional deformation later than 110 Ma. The early NW-SE compression controlled the present bulk architecture of the basin, and the subsequent two tectonic events only caused limited reworking of the previous structures. Through balanced cross-section restoration, we estimate the horizontal shortening ratio of the crust in the study area is over 27% due to the NW-SE compression. Moreover, the contribution of tectonic shortening from the north side of the basin is greater than that from the south side. NW-SE compressional deformation is consistent in time with the episode B of the Yanshanian movement (Yanshanian B), which may be influenced by the subduction of the Paleo-Pacific plate beneath East Asia and the closure of the Mongol-Okhosk Ocean. Subsequent NW–SE extension is likely to be associated with the destruction of the NCC during the Early Cretaceous. Extension may result from the roll-back of the Paleo-Pacific plate and post-orogenic collapse of the Mongol-Okhotsk belt. The last NE-SW compressional event may be linked to the remote effect of the final collision between the Qiangtang and Lhasa terranes.